VİSKOZİTE ÖLÇÜMLERİ İLE (POLİSTİREN ÇÖZÜCÜ) İLİŞKİLERİNİN ARAŞTIRILMASI - KILIÇ, NERMİN (Fırat Üniveristesi, 1994)
Bu çalışmada po1i3tirenin 4ayrı çözücüde 25Tve 35°C' de Huggins sabitleri araştırıldı. Bu amaçla 6 ayrı derişimde polistiren çözeltileri hazırlandı ve her bir çözelti için n3p/C değerleri bulundu. (C : n3p/C) değerleri grafiğe alındığında doğrunun kayması [r\]'yı, eğimi ise k|-j îti 3^ "yi vermektedir. Elde edilen değerlerden kH'ın çözücü cinsi ve polisti renin molekül ağırlığına göre değiştiği gözlendi. Anahtar Kelimeler : Polistiren, Huggins sabiti. Solvent, Molekül ağırlığı

In this study, k^ Muggins constants of polystyrene having different molecular weight have been found for four kinds of solvents at 25°C and 35°C. Having six different concentrations of polu.3tqrene solutions were prepared and n«n/C values were found for each solutions. When the graphs were drawn the values of n3p/C again C, [r\ lvalue of polystyrene was found from the intercept and k^ from the slope of straight line. It was shon that k^ Huggins constants were changet with the molecular weight of polystyrene and the solvent. KEY WORDS : Polystyrene, Huggins constant. Solvent, Molecular weight.
Investigation of (polystyrene-solvent) interaction with the viscosity measurements
Bu tezin, veri tabanı üzerinden yayınlanma izni bulunmamaktadır. Yayınlanma izni olmayan tezlerin basılı kopyalarına Üniversite kütüphaneniz aracılığıyla (TÜBESS üzerinden) erişebilirsiniz.
Keywords: Kimya; Chemistry